Improving Students’ Self Efficacy through QuizWhizzer in Food and Beverage Service Learning - Baiq Maria Ulfa; Nunung Nurjanah; Yetti Setyorini (Universitas Negeri Padang, 2026)
The low level of students' self-efficacy in studying food and beverage service, as seen by their lack of confidence, reliance on teachers, and minimal involvement in class activities, served as the impetus for this study. This study's goals were to: (1) describe how interactive quizzes utilizing QuizWhizzer are implemented; and (2) investigate how these quizzes affect students' self-efficacy. A two-cycle Classroom Action Research (CAR) design was used in this study. Thirty-four students from SMKN 3 Malang's Class XI Industrial participated. Observations, self-efficacy surveys, interviews, and documentation were used to gather data. With scores of 95.00% in Cycle I and 96.67% in Cycle II, the observation findings showed that the execution of learning activities in both cycles was classified as very good. Even though the gain was only 1.67%, it showed that the learning process was consistently implemented and that students' self-efficacy had significantly improved. The questionnaire findings revealed that students' self-efficacy increased from 81.09% in Cycle I to 90.32% in Cycle II, with both results classified as very high. Furthermore, the Wilcoxon Signed Rank Test showed a statistically significant difference between the two cycles (Z = -4.639; p = 0.001). These findings suggest that the use of QuizWhizzer-based interactive quizzes can effectively enhance students' self-efficacy in Food and Beverage Service learning.